2021
DOI: 10.1002/ijgo.13605
|View full text |Cite
|
Sign up to set email alerts
|

Process of fetal head descent as recorded by ultrasonography: How does this compare with the conventional first stage of labor?

Abstract: Objective: To construct an ultrasound partogram using serial transperineal sonographic measurements of the angle of fetal head progression during the first stage of labor, and to compare it with a conventional partogram based on digital vaginal examinations.Methods: Between 2017 and 2018, a prospective cohort study at Drum Tower Hospital, Nanjing, China, recruited 375 nulliparous women with singleton pregnancy and spontaneous onset of labor at 37 or more gestational weeks. Transperineal ultrasound scans were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In a study comparing serial measurements of the AOP and DVE of cervical dilatation during the first stage of labor in singleton nulliparous women, a similar pattern was observed. Using a threshold of 119° for the AOP and 4 cm for the DVE as inflection points, it was observed that there was a significant average difference at 5.5 hours compared to 2.5 hours [ 22 ]. Moreover, the mean msAOP values of 124.3° corresponded to station 0, 145.6° to station +1, 149.4° to station +2, and 178.0° to station +3, during the active phase of the first stage of labor [ 23 ].…”
Section: The Usefulness Of Aop According To Labor Stagesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study comparing serial measurements of the AOP and DVE of cervical dilatation during the first stage of labor in singleton nulliparous women, a similar pattern was observed. Using a threshold of 119° for the AOP and 4 cm for the DVE as inflection points, it was observed that there was a significant average difference at 5.5 hours compared to 2.5 hours [ 22 ]. Moreover, the mean msAOP values of 124.3° corresponded to station 0, 145.6° to station +1, 149.4° to station +2, and 178.0° to station +3, during the active phase of the first stage of labor [ 23 ].…”
Section: The Usefulness Of Aop According To Labor Stagesmentioning
confidence: 99%
“…These observations were made using a reference AOP threshold of 125° [ 17 , 25 ]. With an AOP cutoff value of 93°, the TTD was observed as 12 hours and 12 minutes for nulliparous women and 8 hours and 26 mintues for multiparous women ( Table 2 ) [ 22 , 27 ]. Therefore, there was a discernible negative correlation between AOP values and TTD.…”
Section: The Usefulness Of Aop According To Labor Stagesmentioning
confidence: 99%
“…The authors found that their labor curve based on AoP had a pattern similar to that based on cervical dilatation. 44 The fetal attitude can have an impact on fetal head station and ultimately labor outcome. The fetal attitude can be assessed with transabdominal ultrasound, the occiput-spine angle, as described by Ghi et al 45 A sagittal view of the fetal head and upper spine is acquired when the fetus is in an OA position.…”
Section: Ultrasound Assessment Of Fetal Stationmentioning
confidence: 99%